Scenario of Newborn Care Practices in Private Healthcare Setting in India: An Insights From NFHS-5 Survey - Jimeet Soni; Tapasvi Puwar; Bhavna Puwar (Medsci Publications, 2024)
Background: The private sector contributes significantly to health care service delivery in India. Study shows the prevalence of newborn care practices like early initiation of breastfeeding, kangaroo mother care, and hepatitis B birth dose practices in private sector hospitals across India. Methods: We conducted a basic analysis of unit-level data from the NFHS-5 survey; to understand the newborn care practices in private hospitals in India. Result: The place of the delivery has a significant impact on newborn care practices like kangaroo mother care, early breastfeeding within an hour of birth, and hepatitis-B vaccination at birth. The private sector accounts for 20.73 percent of deliveries wherein, 39.56 percent of private sector hospitals follow EIBF practice. Pre-lacteals were provided to 14.95 percent of the children within the first three days after birth. The better practice of kangaroo mother care was seen in the public sector. The prevalence of the hepatitis B vaccine at birth is very low with 3.25 percent in India.